2005
DOI: 10.1071/sr04044
|View full text |Cite
|
Sign up to set email alerts
|

Total soil organic matter and its labile pools following mulga (Acacia aneura) clearing for pasture development and cropping 1. Total and labile carbon

Abstract: Mulga (Acacia aneura) dominated vegetation originally occupied 11.2 Mha in Queensland, of which 12% has been cleared, mostly for pasture production, but some areas are also used for cereal cropping. Since mulga communities generally occupy fragile soils, mostly Kandosols and Tenosols, in semi-arid environments, clearing of mulga, which continues at a rate of at least 35 000 ha/year in Queensland, has considerable impact on soil organic carbon (C), and may also have implications for the greenhouse gas emissions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 25 publications
7
15
0
1
Order By: Relevance
“…Our results show that the association and retention of C from added microbial residues is a function of differences in stabilization processes among fractions. Our findings are in agreement with previous reports that mineral-associated C, by intra-aggregate occlusion or binding to soil particles (i.e., the OLF and DF, respectively) is more stable than uncomplexed C (as in the FLF) (Dalal et al 2005;Rasmussen et al 2005;Swanston et al 2005;Rasmussen et al 2006;Wagai et al 2009). However at PR, the microbial C inputs were more quickly mineralized in all fractions relative to CA, which we attribute to greater precipitation and higher temperatures in PR, and possibly other edaphic factors such as greater faunal activity at PR.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results show that the association and retention of C from added microbial residues is a function of differences in stabilization processes among fractions. Our findings are in agreement with previous reports that mineral-associated C, by intra-aggregate occlusion or binding to soil particles (i.e., the OLF and DF, respectively) is more stable than uncomplexed C (as in the FLF) (Dalal et al 2005;Rasmussen et al 2005;Swanston et al 2005;Rasmussen et al 2006;Wagai et al 2009). However at PR, the microbial C inputs were more quickly mineralized in all fractions relative to CA, which we attribute to greater precipitation and higher temperatures in PR, and possibly other edaphic factors such as greater faunal activity at PR.…”
Section: Discussionsupporting
confidence: 94%
“…Chemical characterization of this fraction, along with the lesser stability of microbial C inputs throughout the course of our study, is also consistent with reports that the FLF does not strongly promote the stabilization of microbial C; but rather the FLF is likely a more plant derived pool with a fast-turnover (Bird et al 2008;Dalal et al 2005;Rasmussen et al 2005;Wagai et al 2009). …”
Section: Discussionsupporting
confidence: 88%
“…1. This figure was generated by combining data from 20 published studies across Australian agro-ecosystems (Dalal and Mayer, 1986;Bell et al, 1995;Chan et al, 1995;Cogle et al, 1995;Conteh et al, 1997;Whitbread et al, 1998;Sparrow et al, 1999;Skjemstad et al, 2001;Bruand and Gilkes, 2002;Knowles and Singh, 2003;Murphy et al, 2003;Dalal et al, 2005;Young et al, 2005;Wilson et al, 2008; Table 2). The data shows an exponential loss of soil C after the cultivation, with most loss occurring in the first 10 years (Fig.…”
Section: Australian Conditionsmentioning
confidence: 99%
“…In buffelgrass pasture, Dalal et al (2005) detected a greater proportion of C 4 -grass derived SOC and a decline in SOC quality compared to that of the original mulga (Acacia aneura) ecosystem. It was proposed that pasture soils dominated by African grasses gain C because exotic grasses sequester C deeper into the soil than native grasses (Fisher et al 1994), but a meta-analysis of the effects of forest-topasture conversion showed that soil C stocks may either increase or decrease in regions with <1,000 mm mean annual rainfall (Guo and Gifford 2002).…”
Section: Discussionmentioning
confidence: 90%